Imported Methicillin-Resistant Staphylococcus aureus, Sweden - Mikael Stenhem; Åke Örtqvist; Håkan Ringberg; Leif Larsson; Barbro Olsson-Liljequist; Sara Hæggman; Mats Kalin; Karl Ekdahl (Emerging Infectious Diseases, 2010)
Countries such as Sweden that have a low prevalence of methicillin-resistant Staphylococcus aureus (MRSA) offer the opportunity to discern and study transmission of imported cases of MRSA. We analyzed 444 imported cases of MRSA acquisition reported in Sweden during 2000–2003. Risk for MRSA in returning travelers ranged from 0.1 (95% confidence interval [CI] 0.01–0.4) per 1 million travelers to Nordic countries to 59.4 (95% CI 44.5–79.3) per 1 million travelers to North Africa and the Middle East. Most imported cases (246, 55%) were healthcare acquired, but regions with the highest risk for MRSA in travelers showed a correlation with community acquisition (r = 0.81, p = 0.001). Characteristic differences in MRSA strains acquired were dependent on the region from which they originated and whether they were community or healthcare acquired. Knowledge of differences in transmission of MRSA may improve control measures against imported cases.